2010
DOI: 10.13005/msri/070114
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of α - amylase from locale bacteria isolate Bacillus subtilis ITBCCB148 with diethylaminoethyl cellulose (DEAE-Cellulose)

Abstract: The thermal stability increase of a-amylase obtained from locale bacteria isolate Bacillus subtilis ITBCCB148 was achieved by immobilization process using an ionic exchange matrix of DEAE-Cellulose. The result showed that the immobilized enzyme has an optimum temperature of 60°C; KM 14.8 mL substrate and Vmax 42.4 U/mL. The thermal stability storage temperature of 60°C, pH 9.0 and 60 minutes demonstrated the immobilized enzyme has residual activity of 28.1%; ki = 0.0224 min.-1; and ΔGi = 103.7 kJ mol-1. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some previous researches performed with immobilization and chemical modification have shown that the enzymes obtained have significantly increased their stability against pH and temperature compared to the native enzyme (Yandri, et al, 2008(Yandri, et al, , 2010a(Yandri, et al, , 2010bGermain dan Crichton, 1988;Cordt, et al, 1992;Steadman, et al, 1991;Skerker dan Clark, 1987;Rani, et al, 2007;Reshmi, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous researches performed with immobilization and chemical modification have shown that the enzymes obtained have significantly increased their stability against pH and temperature compared to the native enzyme (Yandri, et al, 2008(Yandri, et al, , 2010a(Yandri, et al, , 2010bGermain dan Crichton, 1988;Cordt, et al, 1992;Steadman, et al, 1991;Skerker dan Clark, 1987;Rani, et al, 2007;Reshmi, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The binding in the adsorption method is normally occurred by ionic and covalent bond. The uses of support matrix containing either anionic or cationic exchange residues as immobile matrix has some advantages as the bond formed is relatively stable (Yandri, et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization process on -amylase from B.subtilis ITBCCB148 has successfully increased the enzyme stability at high temperature using diethylaminoethyl cellulose (DEAE-Cellulose) 8 ; carboxymethyl cellulose (CM-Cellulose) 9 ; and bentonite 10, 11 , calcium alginate 12 although the increase was only 1.5; 3.67 and 2.12, however, the immobilized enzymes could be used between 5-6 times. Immobilization on -amylase has also been performed using amberlite 13 and gelatin 14 where they have successfully increased the stability of this enzyme.…”
Section: Introdcutionmentioning
confidence: 99%
“…Research phases performed were production, isolation, purification and characterization of the purified (native) enzyme similar to the procedures previously reported 9 .…”
Section: Research Phasesmentioning
confidence: 99%